Context-dependent autoprocessing of human immunodeficiency virus type 1 protease precursors - Tien, ChihFeng (PLoS One, 2018)
HIV-1 protease autoprocessing is responsible for liberation of free mature protease (PR) from the Gag-Pol polyprotein precursor. A cell-based model system was previously developed to examine the autoprocessing mechanism of fusion precursors carrying the p6*-PR miniprecursor sandwiched between various proteins or epitopes. We here report that precursor autoprocessing is context-dependent as its activity and outcomes can be modulated by sequences upstream of p6*-PR. This was exemplified by the 26aa maltose binding protein (MBP) signal peptide (SigP) when placed at the N-terminus of a fusion precursor. The mature PRs released from SigP-carrying precursors are resistant to self-degradation whereas those released from SigP-lacking fusion precursors are prone to self-degradation. A H69D mutation in PR abolished autoprocessing of SigP-containing fusion precursors whereas it only partially suppressed autoprocessing of fusion precursors lacking SigP. An autoprocessing deficient GFP fusion precursor with SigP exhibited a subcellular distribution pattern distinct from the one without it in transfected HeLa cells. Furthermore, a SigP fusion precursor carrying a substitution at the P1 position released the mature PR and PR-containing fragments that were different from those released from the precursor carrying the same mutation but lacking SigP. We also examined autoprocessing outcomes in viral particles produced by a NL4-3 derived proviral construct and demonstrated the existence of several PR-containing fragments along with the mature PR. Some of these resembled the SigP precursor autoprocessing outcomes. This finding of context-dependent modulation reveals the complexity of precursor autoprocessing regulation that most likely accompanies sequence variation imposed by the evolution of the upstream Gag moiety.